2015
DOI: 10.1523/jneurosci.2453-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Bax Regulates Neuronal Ca2+Homeostasis

Abstract: Excessive Ca 2ϩ entry during glutamate receptor overactivation ("excitotoxicity") induces acute or delayed neuronal death. We report here that deficiency in bax exerted broad neuroprotection against excitotoxic injury and oxygen/glucose deprivation in mouse neocortical neuron cultures and reduced infarct size, necrotic injury, and cerebral edema formation after middle cerebral artery occlusion in mice. Neuronal Ca 2ϩ and mitochondrial membrane potential (⌬ m ) analysis during excitotoxic injury revealed that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 115 publications
4
45
0
2
Order By: Relevance
“…Scale bar = 100 μm Previous studies showed that a rise of calcium concentration signals an increased cellular energy demand and mediates a number of pathways that can precipitate mitochondrial injury and cell death [9]. Of interest, increments in [Ca 2+ ] c are detected at the acute phases after MCAO [10][11][12]. At approximately the same time, the expression of MCU is up-regulated [13].…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar = 100 μm Previous studies showed that a rise of calcium concentration signals an increased cellular energy demand and mediates a number of pathways that can precipitate mitochondrial injury and cell death [9]. Of interest, increments in [Ca 2+ ] c are detected at the acute phases after MCAO [10][11][12]. At approximately the same time, the expression of MCU is up-regulated [13].…”
Section: Discussionmentioning
confidence: 99%
“…Важно отметить, что гиперпродукция белка Bcl-2 у детей с ло-кально обусловленной эпилепсией направлена на стабилизацию кальциевого гомеостаза. Было показано, что увеличение концентрации белка Bcl-2 предотвращает выход внутриклеточного кальция из эндоплазматического ретикулума, усиливая его обратный захват, а также потенци-рует увеличение пассивного транспорта кальция в митохондрии и ингибирует вхождение ионов кальция в ядро [10,19]. Следовательно, высокая активность окислительных процессов у больных ДЦП и существующая кальций-зависимая ги-первозбудимость при эпилепсии создают усло-вия для повышенного синтеза белка Bcl-2.…”
Section: рис концентрация белка Bcl-2 (нг/мл) в исследуемых группахunclassified
“…Изучены молекулярные механиз-мы, с помощью которых белки семейства Вс1-2 регулируют апоптоз: это митохондриальный путь и процесс активации каспаз [7,8,9]. Известно, что белок Bcl-2 участвует в поддержании кле-точного гомеостаза ионов кальция, регулируя по-ток кальция через эндоплазматический ретику-лум [10,11]. Несмотря на то, что ключевая роль в регуляции апоптоза для онкогена Bcl-2 уста-новлена давно и не вызывает сомнения [12], мо-лекулярный механизм действия этого антиапоп-тотического белка при эпилепсии не выяснен.…”
unclassified
“…However, excessive glutamate is associated with numerous neurological disorders including stroke, traumatic brain injury [2,3], multiple sclerosis, Huntington's disease, Parkinson's disease and Alzheimer's disease [4]. Excessive glutamate can over activate glutamate receptors and result in high calcium ion (Ca 2+ ) influx, which activates a number of enzymes that damage cell structures such as the cell membrane, cytoskeleton components and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-3, a member of the caspase family, determines the incidence of apoptosis. The members of the Bcl-2 family such as Bcl-2 and Bax proteins are the most prominent factors in the mitochondria-mediated apoptotic pathway [3,9]. Studies have shown the powerful properties of various natural polyphenols against neuronal exitotoxicity induced by NMDA [10,11].…”
Section: Introductionmentioning
confidence: 99%